Examining Social Presence and Online Learning Satisfaction Among Malaysian University Students During the COVID-19 Pandemic - Ho, Meng Chuan; Keoy, Kay Hooi; Tan, Han Leong; Pang, Khong Yun *; Ooi, Pei Boon *; Rohana, Yusof (Global Academic Excellence (M) Sdn Bhd, 2022)
This study aimed to investigate the relationship between social presence and online learning satisfaction among 257 university students (Mage=19.89years, SDage=1.93) during the COVID-19 pandemic. The partial least square (PLS) algorithm was used to examine the association and the prediction of the proposed relationship. This study employed a cross-sectional research design with convenience sampling. Participants completed an online survey questionnaire which consisted of a Social Presence Scale and Satisfaction Scale in March 2022. All scales included in the present study reported a satisfying level of reliability and validity coefficient. The PLS regression tests showed that social presence was positively associated with online learning satisfaction (β = 0.717, p < 0.01). Additionally, social presence reported a medium level of prediction power towards online learning satisfaction which shed light on the underlying mechanisms that explain students’ online learning satisfaction during the COVID-19 pandemic. The results also demonstrate the singifiant contribution of teaching and learning approach, programme or intervention to facilitate social presenc. It is also essential to promote a greater sense of online satisfaction among university students.